Women participation in rooftop gardening in some areas of Khulna city (Bangladesh Journal of Agricultural Research, 2019)
Khulna is the largest city corporation in the southwestern region of Bangladesh where rooftop gardening is gradually gaining popularity among the city dwellers. The main purpose of the study was to assess the extent of participation of women in rooftop gardening in Khulna city and to explore the relationship between each of the selected characteristics of women and their extent of participation in rooftop gardening. Primary data were collected from randomly selected 92 women during the period of 20 March to 10 April, 2018 at Rayermahal, Khalishpur, Daulatpur and Maheshwarpasha areas under Khulna city. Most (94.57%) of the women had medium participation, 3.26% had high participation, and 2.17% had low participation. Considering four aspects, the women had higher participation in preparatory stage (Participation Extent (PE) = 59.87%) whereas it was least in harvesting stage (PE = 34.06%). Considering the twenty issues under four aspects of rooftop gardening, the highest participation by the women was in watering the garden (PE = 88.04%) and no participation was in marketing (PE = 0%). Among ten selected characteristics level of education (P